Learning styles among students of the University of Sulaimani - فتاح, فەرمان فایق فتاح; محمد, أ.م.د. عبدالصمد أحمد محمد (Sulaimani Journal for Humanities, 2025)
The aim of this study is to determine the level of learning styles among students of Sulaimani University, as well as to determine the level of learning styles according to the variable of gender, college. The researchers used descriptive relationship method. The research community consists of all students of Sulaimani University for the academic year (2024-2025) in the morning class, which number (20629) students. A sample of 1022 male and female students was randomly selected from the appropriate class levels. The study employed a researcher-constructed criterion to assess learning methods. The criterion's validity and reliability were established prior to its implementation. The most important statistical tools used are arithmetic mean, standard deviation, Person's correlation coefficient, Cronbach's alpha, t-test, ANOVA. Finally, the researchers reached a number of conclusions Recommendations, which are the most important findings of the study: 1. The level of learning methods among university students is generally high. 2. The statistical difference in the level of learning methods among university students according to gender variables (male and female) is in favoring of females. 3. There is no statistically significant difference in learning styles according to college affiliation.
Keywords: Learning; learning styles